(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article examines the theoretical foundations of forming green spaces and eco-cities within modern urban environments. The research highlights the importance of integrating ecological balance, technological innovation, and sustainable planning to ensure harmony between humans and nature. It discusses the essential principles of eco-city development, including sustainable land use, renewable energy systems, waste recycling, and public participation. Furthermore, the study analyzes the ecological, aesthetic, and social roles of green spaces in improving urban life quality. Special attention is given to the concept of green infrastructure and its role in mitigating climate change, enhancing biodiversity, and promoting public health. The article concludes that forming green spaces and eco-cities is a key step toward achieving long-term urban sustainability and environmental resilience.